2022
DOI: 10.3390/v14112473
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 at the Human–Animal Interface: Implication for Global Public Health from an African Perspective

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has become the most far-reaching public health crisis of modern times. Several efforts are underway to unravel its root cause as well as to proffer adequate preventive or inhibitive measures. Zoonotic spillover of the causative virus from an animal reservoir to the human population is being studied as the most likely event leading to the pandemic. Consequently, it is important to consider viral evolution and the process of spread within zoonotic anthropogenic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…To understand the ecology and epidemiology of potentially zoonotic pathogens in Nigeria and elsewhere, focused One Health monitoring of possible animal reservoirs in addition to those animals that may have been exposed are important steps in pandemic preparedness [ 35 ]. In the present study, SARS-CoV-2 RBD ELISA reactive sera were found in feral dogs, rabbits, and two pangolins.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the ecology and epidemiology of potentially zoonotic pathogens in Nigeria and elsewhere, focused One Health monitoring of possible animal reservoirs in addition to those animals that may have been exposed are important steps in pandemic preparedness [ 35 ]. In the present study, SARS-CoV-2 RBD ELISA reactive sera were found in feral dogs, rabbits, and two pangolins.…”
Section: Discussionmentioning
confidence: 99%